Reflections of nurses and primary healthcare managers on integrating hospital at home into public primary healthcare services: a Norwegian focus group study - Lillian Karlsen; Bente Prytz Mjølstad; Bjarte Bye Løfaldli; Anne-Sofie Helvik (Taylor & Francis Group, 2024)
Background Hospital at home (HaH) is an innovative approach to healthcare delivery that brings specialized services to patients' homes. HaH services are typically available in urban areas where hospitals can easily reach nearby patients. An integrated care model that utilizes the public primary healthcare system may extend HaH services to include patients residing further away from hospitals. However, there is limited evidence of primary healthcare employees' views on integrating HaH care into primary healthcare services. This study aimed to explore the reflections of primary healthcare employees on integrating HaH care into primary healthcare services.Methods Ten focus group interviews were conducted with homecare nurses and managers of primary healthcare services in five municipalities in Mid-Norway. Reflexive thematic analysis was used to analyze the data.Results The analysis resulted in three key themes regarding the integration of HaH care into primary healthcare. Participants discussed how they capture the distinctiveness of HaH care within the primary healthcare landscape. Moreover, they identified that the introduction of HaH care reveals opportunities to address challenges. Lastly, the study uncovered a strong primary healthcare commitment and a sense of professional pride among the participants. This resilience and dedication among primary healthcare employees appeared as an incentive to make the integration of HaH work.Conclusions This study offers valuable insights into integrating HaH into primary healthcare services, highlighting opportunities to address challenges. The resilience and dedication of primary healthcare employees underscore their commitment to adapting to and thriving with HaH care. To establish a sustainable HaH care model, it is important to address geographical limitations, consider the strain on providers, maintain robust relationships, enhance funding, and formalize decision-making processes.